An industrial quality control study on Splash Corporation - Borromeo, Levy Martin (College of Engineering, 2006)
With increasing competition amongst companies in the personal and skin care industry, a carefully crafted and well-implemented Statistical Process Control program is necessary to ensure product quality, reduced wastage, and increased customer satisfaction. One principle that underlies this study is to present to the Management of Splash Corporation a way of "doing things right the first time". A Pareto Chart was used to identify the product to focus on and the SkinWhite brand which accounts for 31% of revenues was chosen. SkinWhite has several variants such as face creams, soaps, lotions, and face wash. The team selected the SkinWhite Hand and Body Lotion which is the variant with the most sales-to-outlets quantity. The present production system was documented in detail and the processes involved in the production of SkinWhite Lotion were studied carefully. Interviews were conducted with workers directly involved in the operations to identify problems in the production. An interview with the quality assurance analyst addressed the problems regarding inspections and quality system. Problem analyses lead to the identification of 15 core problems and five secondary problems. The primary problems identified in this study are lack of quality control training, lack of deployment of quality tools, and inappropriate sampling raw materials inspection plan. Lack of quality control training and knowledge in SPC is evident in the control charts that are being used by Splash where control limits are computed based on specification limits and not from sample data. The lack of deployment of quality tools is evidenced by frequent machine breakdown because of the inability to predict future downtimes that can be done with the use of sampling technique. It can be seen that the sampling plan used by Splash has a high lot tolerance percent defective as the sample size increase which is undesirable. Control charts were constructed with the aid of statistical software. The out-of-control points were removed and were identified to have assignable causes. Once the processes are in control, process capability analyses were conducted. It has been found that the process is not capable of producing SkinWhite Lotion SPF20 within specification limits. Some of the recommendations of the study were to hire an industrial engineer or a statistician to construct and interpret quality tools, to train employees to deploy quality tools and analyze control charts, and to implement a Dodge-Roming Chain Sampling Plan for raw materials inspection.